Chemical communication of predation risk in zebrafish does not depend on cortisol increase - Barcellos, Leonardo J. G.; Koakoski, Gessi; Rosa, Joao G. S. da; Ferreira, Daiane; Barreto, Rodrigo E. [UNESP]; Giaquinto, Percilia C. [UNESP]; Volpato, Gilson L. [UNESP] (Nature Publishing Group, 2014)
We investigated chemical cues among groups of zebrafish (Danio rerio) when communicating information about the risk of predation. We found that visual cues of the predator (tiger Oscar, Astronotus ocellatus) did not increase whole-body cortisol levels in groups of zebrafish but that water conditioned by these (donor) zebrafish stressed (target) conspecifics, thereby increasing whole-body cortisol. This finding was confirmed when these zebrafish groups were in different aquaria and communicated exclusively via water transfer. This result indicates that the stress induced in the target zebrafish does not depend on an increase in whole-body cortisol levels in the donor zebrafish. Because cortisol participation is rejected in this predation-risk communication, other chemicals from the stress systems should be investigated.